Hemagglutination inhibiting antibodies and protection against seasonal and pandemic influenza infection. - Fox, A; Mai, L; Thanh, LT; Wolbers, M; Le Khanh Hang, N; Thai, P; Thi Thu Yen, N; Minh Hoa, L; Bryant, J; Duong, T; Thoang, D; Barr, I; et al. (2015)
OBJECTIVES: Hemagglutination inhibiting (HI) antibodies correlate with influenza vaccine protection but their association with protection induced by natural infection has received less attention and was studied here. METHODS: 940 people from 270 unvaccinated households participated in active ILI surveillance spanning 3 influenza seasons. At least 494 provided paired blood samples spanning each season. Influenza infection was confirmed by RT-PCR on nose/throat swabs or serum HI assay conversion. RESULTS: Pre-season homologous HI titer was associated with a significantly reduced risk of infection for H3N2 (OR 0.61, 95%CI 0.44-0.84) and B (0.65, 95%CI 0.54-0.80) strains, but not H1N1 strains, whether re-circulated (OR 0.90, 95%CI 0.71-1.15), new seasonal (OR 0.86, 95%CI 0.54-1.36) or pandemic H1N1-2009 (OR 0.77, 95%CI 0.40-1.49). The risk of seasonal and pandemic H1N1 decreased with increasing age (both p < 0.0001), and the risk of pandemic H1N1 decreased with prior seasonal H1N1 (OR 0.23, 95%CI 0.08-0.62) without inducing measurable A/California/04/2009-like titers. CONCLUSIONS: While H1N1 immunity was apparent with increasing age and prior infection, the effect of pre-season HI titer was at best small, and weak for H1N1 compared to H3N2 and B. Antibodies targeting non-HI epitopes may have been more important mediators of infection-neutralizing immunity for H1N1 compared to other subtypes in this setting.